(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Leukocyte count, erythrocyte sediment rate and C-reactive protein are available laboratory markers which may be helpful in prediction of technetium Tc 99m dimercaptosuccinic acid (DMSA) renal scintigraphy results. None of these, however, have enough accuracy for prediction of renal injury and scar. This study was aimed to evaluate the diagnostic accuracy of urinary β2-microglobulin in detection of renal injury in children with acute pyelonephritis. Materials and Methods. Eighty-nine children between 2 months and 14 years old with the diagnosis of acute pyelonephritis that had no past history of infection in the urinary tract system were enrolled in the study. A standard urine sample according to patients’ age was obtained for urine culture, urinalysis, and urinary β2-microglobulin tests. Blood sample was obtained for leukocyte count, creatinine, blood urea nitrogen, C-reactive protein, erythrocyte sediment rate, and electrolytes tests. All patients underwent DMSA scan. Results. The cutoff point for urinary β2-microglubulin for prediction of positive DMSA scan was 0.8 mg with a sensitivity of 40.9% (95% CI, 26.3% to 56.8%) and a specificity of 84.1% (95% CI, 69.9% to 93.4%), a positive predictive value of 72.0% (95% CI, 50.6% to 87.9%) and an negative predictive value of 58.7% (95% CI, 45.6% to 71.0%). Conclusions. Urinary β2-microglobulin is not enough sensitive and specific to be used as a diagnostic marker for prediction of renal injury. Other common markers such as erythrocyte sediment rate, leukocyte count, and C-reactive protein can be used in combination to predict kidney injury in children with acute pyelonephritis.